Effects of a Rosiridin against Rotenone-induced Rats Model of Parkinson's Disease: In-vivo Study and in silico Molecular Modeling - Rafeeq, Misbahuddin; Al-Abbasi, Fahad A.; Afzal, Muhammad; Alharbi, Khalid Saad; Moglad, Ehssan; Al-Qahtani, Salwa D.; Bukhari, Hussam A.; Imam, Faisal; Sayyed, Nadeem; Kazmi, Imran (Current Neuropharmacology, 2025)
AimThe investigation aimed to study the outcome of rosiridin in Parkinson's disease (PD) induced by rotenone (ROT) in rodents.MethodsRodents were randomized into IV groups and were induced with ROT followed by treatment with rosiridin. Group I-IV received saline as a vehicle, II-ROT (0.5 mg/kg S.C) for 28 consecutive days, III and IV- rosiridin 10 and 20 mg/kg orally with ROT. On completion of the experimental duration, behavioral investigations were carried out. Biochemical variables such as acetylcholinesterase (AChE), oxidative stress and antioxidants markers (Malondialdehyde-MDA, glutathione-GSH, superoxide dismutase-SOD, and catalase-CAT), anti-inflammatory (Interleukin-1 beta-IL-1β, IL-6, and tumor necrosis factor alpha-TNF-α), alteration in neurotransmitters (Serotonin-5-HT), norepinephrine, and dopamine-DA, along with metabolites such as 5-hydroxy indole acetic acid (5-HIAA), mitochondrial complex I, II, IV, and caspase-3 activity were evaluated at the end of the experiment. Furthermore, molecular docking and dynamics were performed for target ligands.ResultsRosiridin significantly restored the level of AChE, oxidative stress and antioxidants markers (MDA, GSH, SOD, and CAT), anti-inflammatory (IL-1β, IL-6, and TNF-α), alteration in neurotransmitters, mitochondrial complex I, II, IV, and caspase-3 activity. Rosiridin has a favorable negative binding affinity to AChE (-8.99 kcal/mol). The results of the molecular dynamics simulations indicate that proteins undergo a substantial change in conformational dynamics when binding to rosiridin.ConclusionIn this study, rosiridin may exhibit neuroprotective properties against the Parkinson's model for treating PD.
Keywords: rotenone